2020
DOI: 10.1039/d0ob01974g
|View full text |Cite
|
Sign up to set email alerts
|

Regioselectivity in the adiabatic photocleavage of DNA-based oxetanes

Abstract: Direct absorption of UVB light by DNA may induce formation of cyclobutane pyrimidine dimers and pyrimidine-pyrimidone (6-4) photoproducts. The latter arise from the rearrangement of unstable oxetane intermediates, which have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…S4 in the ESI†) under the same experimental conditions (the results obtained at λ exc = 310 and 266 nm were the same); this revealed that the photocleavage of BQ-Ox decays to the ground state of the photoproducts, in contrast with previous results on BP-Thy or BP-Ura oxetanes, where certain degree of “adiabaticity” in the photoinduced cycloreversion process was observed. 19,22,23,25…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S4 in the ESI†) under the same experimental conditions (the results obtained at λ exc = 310 and 266 nm were the same); this revealed that the photocleavage of BQ-Ox decays to the ground state of the photoproducts, in contrast with previous results on BP-Thy or BP-Ura oxetanes, where certain degree of “adiabaticity” in the photoinduced cycloreversion process was observed. 19,22,23,25…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16][17] In this regard, since the primary Thyh<iThy dimers are not isolable due to their chemical instability, 18 a variety of model oxetane conjugates composed of benzophenone (BP) and thymine (Thy) or uracil (Ura) derivatives have been employed in order to investigate the mechanism of photoinduced ring opening by means of spectroscopic techniques. [19][20][21][22][23] Although these models are far from the real Thyh<iThy dimers, the BP moiety has been found to be convenient to follow the course of the photoreaction by transient absorption spectroscopy, which allows rapid and quantitative detection of the BP triplet excited state ( 3 BP*), 24 amongst other transient species. Interestingly, irradiation of BP-Thy and/or BP-Ura oxetanes results in some cases in a rare ''adiabatic'' ring splitting process involving diradical species and triplet exciplexes, which ultimately evolve leading to the formation of 3 BP* and Thy (or Ura) in its ground state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Nevertheless, due to the existence of the seven-atom linking bridge of the BZP-Thy dyad and its strain release of the macrocycle cleavage, we didn't find the singlet diradical intermediate, resulting in the pretty fast photoinduced ring-opening rate of the BZP-Thy dyad. 21,54…”
Section: Energetically Favorable Pathways Of Bzp-photosensitized Thym...mentioning
confidence: 99%
“…[34][35][36][37] It has also been proven that ultrafast electron transfer is markedly influenced by the relative orientation and the distance between the individual chromophores in bichromophoric linked systems. [38][39][40] In general, the location and spatial arrangement of a linked or bound drug are highly relevant to understand the kinetics and yields of the photoinduced processes occurring both in covalently attached drug-amino acid systems and in non-covalent drug-protein complexes.…”
Section: Introductionmentioning
confidence: 99%